Effect of Cytoplasm Types T and D on Quantitative Trait Loci for Chip Color and Proline Content in Potato Tubers in a Diploid Potato Population - Paulina Smyda-Dajmund; Katarzyna Szajko; Dorota Sołtys-Kalina; Waldemar Marczewski; Jadwiga Śliwka (Agronomy)
The production of chips is an increasing part of the potato market. While the potato tubers are stored at low temperatures to minimize storage problems, they tend to accumulate reducing sugars, which negatively impact the quality and color of fried products. The goal of this study was to analyze the impact of cytoplasm type on chip color after harvest and after cold storage at 4 °C, as well as on proline content in cold-stressed potato tubers in a diploid potato population obtained from reciprocal crossing of parents with T- and D-type cytoplasm. Using 224 F1 progeny clones genotyped with Diversity Array Technology (DArTseq™), we mapped the Quantitative Trait Loci (QTL), treating cytoplasm type as a covariate. We detected five QTLs for chip color after harvest and six after cold storage, with the strongest QTL for both traits overlapping on chromosome III. Five QTL for proline content were detected on chromosomes V, X and XII, with the most significant one located on chromosome X. Although the progeny clones with T-type cytoplasm produced significantly lighter chips after cold storage, the cytoplasm type used as a covariate caused only minor modifications to the obtained QTL landscapes for chip color and proline content.